Recycling of Organic Wastes through Composting: Process Performance and Compost Application in Agriculture - Sayara, Tahseen; Basheer-Salimia, Rezq; Hawamde, Fatina; Sánchez, Antoni (Agronomy (Basel), 2020)
Composting has become a preferable option to treat organic wastes to obtain a final stable sanitized product that can be used as an organic amendment. From home composting to big municipal waste treatment plants, composting is one of the few technologies that can be practically implemented at any scale. This review explores some of the essential issues in the field of composting/compost research: on one hand, the main parameters related to composting performance are compiled, with especial emphasis on the maturity and stability of compost; on the other hand, the main rules of applying compost on crops and other applications are explored in detail, including all the effects that compost can have on agricultural land. Especial attention is paid to aspects such as the improvement of the fertility of soils once compost is applied, the suppressor effect of compost and some negative experiences of massive compost application.